2007
DOI: 10.1007/s10633-006-9043-8
|View full text |Cite
|
Sign up to set email alerts
|

A primer on motion visual evoked potentials

Abstract: Motion visual evoked potentials (motion VEPs) have been used since the late 1960s to investigate the properties of human visual motion processing, and continue to be a popular tool with a possible future in clinical diagnosis. This review first provides a synopsis of the characteristics of motion VEPs and then summarizes important methodological aspects. A subsequent overview illustrates how motion VEPs have been applied to study basic functions of human motion processing and shows perspectives for their use a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
58
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 203 publications
(178 reference statements)
7
58
2
Order By: Relevance
“…The latency of these differences is consistent with previous studies showing that processing of coherent motion occurs around 170 ms (Heinrich 2007;Kuba et al 2007;Niedeggen and Wist 1999;Mercier et al 2009). During this time window, stronger activations were found for the coherent motion conditions in the posterior temporal, parieto-occipital and parietal regions (see Fig.…”
Section: Vm Control Tasksupporting
confidence: 91%
“…The latency of these differences is consistent with previous studies showing that processing of coherent motion occurs around 170 ms (Heinrich 2007;Kuba et al 2007;Niedeggen and Wist 1999;Mercier et al 2009). During this time window, stronger activations were found for the coherent motion conditions in the posterior temporal, parieto-occipital and parietal regions (see Fig.…”
Section: Vm Control Tasksupporting
confidence: 91%
“…Our study showed that controls and patients with AD differ in motion processing examined by means of the motion-onset VEPs, the main peak of which-N2-was shown to be rather specific for magnocellular pathway/dorsal stream activity [12,26,30,31]. We found a significantly lower amplitude of N2 peak in motion-onset VEPs to radial stimuli placed in the periphery of the visual field (when central 20 deg was masked) in patients with AD when compared with controls, but we did not get a significant difference for full-field radial stimuli as well as for translational motion stimuli.…”
Section: Visual Evoked Potentialsmentioning
confidence: 61%
“…N2)/2) of the main P100 peak and in the M-VEPs peak latencies and inter-peak absolute mean amplitudes ((P1 ? P2)/2-N2) of the N2 peak (this peak was shown to represent the main motionspecific component of this VEP type [7,8,11].…”
Section: Methodsmentioning
confidence: 90%
“…Two types of visual stimuli were used to elicit VEPpattern-reversal and motion-onset stimuli-with the aim of testing the function of the two fundamental subsystems of the visual pathway (magnocellular and parvocellular) and their cortical projections (the dorsal and ventral streams) [6][7][8].…”
Section: Methodsmentioning
confidence: 99%